Handbook of research on nano-drug delivery and tissue engineering : guide to strengthening healthcare systems - Rajendran, Rajakumari; Maria, Hanna J.; Thomas, Sabu; Kalarikkal, Nandakumar (FRLORIDA; APPLE ACADEMIC PRESS, 2022)
"Handbook of Research on Nano-Drug Delivery and Tissue Engineering: Guide to Strengthening Healthcare Systems provides an important and valuable collection of research accomplishments in nanomedicine, drug delivery, tissue engineering, processing, formulations, and their applications. With contributions from leading researchers in the nanomedicine field from industry, academia, and government and private research institutions across the globe, the volume provides an up-to-date record on the major findings and observations in the field of nanomedicine and tissue engineering. Divided into two parts, the book addresses topical issues in nano-drug delivery and nanotechnological approaches to tissue engineering. The first section offers research on a variety of diverse nano-based drug delivery systems, along with discussions of their efficacy, safety, toxicology, and applications for different purposes. Focusing on nanotechnology approaches to tissue engineering, part two of the volume considers the use of hydrogel systems, nanoceria and micro- and nano-structured biomaterials for bone tissue engineering, mesenchymal stem cells, and more. This volume is a systematic scientific reference of the novel research developments specifically in this area. The editors give special emphasis on the new trends and developments in the field of nanomedicine that will be very helpful for pharmaceutical and medical researchers, scientists, faculty, and students"--
Recent Advancements on Polymer-Based Drug Delivery System / Roshni Thapa, Debasish Saha, Ranjita Ghosh Moulick, and Jaydeep Bhattacharya -- Biomedical Application of Polyhydroxybutyrate Biopolymer in Drug Delivery / Md. Asad Khan and M. Moshahid A Rizvi -- Brain Targeting Efficacy Novel Solid Lipid Nanoparticles / N. Jawahar, Lireni C. Humtsoe, and P. B. Anjali -- Nanoclay : A Novel Drug Delivery System for Improved Oral Bioavailability / N. Jawahar, C. Sanjeev, and P. B. Anjali -- Study on Internet of Nanotechnology (IoNT) in a Healthcare Monitoring System / V. J. Chakravarthy, P. Hakkim Devan Mydeen, and M. Seenivasan -- Safety Assessment and Nanotoxicology of Nanomaterials in a Drug Delivery System / Sharida Fakurazi, Mas Jafri Masarudin, and Mohd Zobir Hussein -- Sustainable Development of Polyhydroxyalkanoates and Their Application as an Effective Tool in Drug Delivery and Tissue Engineering / Anupama Shrivastava, Sonam Dubey, Alka Mishra, Sourish Bhattacharya, and Sandhya Mishra -- Tailoring of Intrinsic Physicochemical Properties of Nanoparticles for Antimicrobial Therapy / Swaroop Chakraborty and Superb K. Misra -- Bioinspired Nanofibers : Preparation and Characterization / Poornima Balan, Janani Indrakumar, Anbuthiruselvan Solaimuthu, Padmaja Murali, and Purna Sai Korrapati -- Hydrogel Systems for Tissue Engineering / Senthilkumar Muthusamy, Shiny Velayudhan, and P. R. Anil Kumar -- Injectable Hydrogel Scaffolds for Neural Tissue Engineering Applications / Josna Joseph, Annie Abraham, and Myron Spector -- Nanoceria : A Rare-Earth Nanoparticle for Tissue Engineering Applications / Shiv Dutt Purohit, Hemant Singh, Indu Yadav, Sakchi Bhushan, and Narayan Chandra Mishra -- Micro- and Nanostructured Biomaterials for Bone Tissue Engineering / Ajita Jindal, Jaydeep Bhattacharya, and Ranjita Ghosh Moulick -- Characteristics and Functions of Mesenchymal Stem Cells Derived From Nonosteoarthritis and Osteoarthritis Conditions / Satar Jabbar Rahi Algraittee and Rajesh Ramasamy -- Bioinspired Nanofibers : State of Art in Tissue Regeneration / Poornima Balan, Janani Indrakumar, Anbuthiruselvan Solaimuthu, Padmaja Murali, Aishwarya Satish, and Purna Sai Korrapati -- Phyto-Nano Bioengineered Scaffolds : A Promise to Tissue Engineering Research / Gayathri Sundar, Josna Joseph, Rebu Sundar, Annie John, and Annie Abraham -- Effect of Surface Nanostructuring on Gene Expression for Protein Synthesis, Osteoblast Cells Recruitment and Size of Focal Adhesion : A Review / Nancy Raj, Rahul Agrawal, K. Chattopadhyay, R. Bansal, and V. Singh -- Perspectives on Translational Outcomes Research Using Nanobiotechnological Agents / Shinjini Mitra, Nandita Ghosh, Pramathadhip Paul, Payal Pal, Ranita Bose, Adeti Munmun Sengupta, and Ena Ray Banerjee.
Includes bibliographical references and index.
Keywords: Nanotechnology; Drug Delivery Systems; Tissue Engineering; Nanomedicine